THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND BODY MASS INDEX OF GRAMMAR SCHOOL STUDENTS (Fiep Bulletin - online, 2014)
The purpose of the paper is to find out the level of grammar school students movement activity in Vranov nad Top?ou and analyse the relationship between movement activity and body mass index (BMI ). The research group consisted of 160 girls and 148 boys aged between 15-19 years. For examining the level of movement activity was International Physical Activity Questionnaire (IPAQ). BMI was calculated on the basis of body height and body weight data of respondents. During the processing of data we focused on basic areas of intensive movement activity, average load movement activity, walking practiced during movements and free time, and sitting during working (school attendance days) and weekend days. We found out that difference between movement activity practicing of girls and boys on the behalf of boys. In term of movement activity and inactivity, movement inactivity had greater share during day. Students spend at average more than 8.7 hours by sitting during school-time and more than 7 hours during weekend. Movement activity data were related to body mass index. On the basis of correlation, there was not found any relation. Acknowledgment: The thesis was supported by Slovak Research and Development Agency on the basis of agreement APVV - 0768-11.
Keywords: physical inactivity; International Physical Activity Questionnaire (IPAQ); vigorous movement activity; moderate load movement activity